Evaluation of volumetric dimensional changes in posterior extraction sites with and without ARP using a novel imaging device. (14th September 2017) - Sbordone, Carolina; Toti, Paolo; Martuscelli, Ranieri; Guidetti, Franco; Porzio, Massimo; Sbordone, Ludovico
Abstract: Background: Alveolar ridge volume loss may be minimized when postextraction sockets are filled by bone substitutes. Purpose: The aim of the study was to measure the effect of alveolar ridge preservation (ARP) in maintaining the external contour of the ridge after fresh socket grafting with or without particulate anorganic bovine bone mineral (BBM) and resorbable barrier covering. Materials and methods: In the present controlled study, patients subjected to single‐tooth extraction were allocated to 2 groups: postextraction sockets grafted with bovine bone mineral ( bbm ), and naturally healing sockets ( nat ). Before and at 5 months following tooth extraction, plaster cast contours of the sockets were acquired by means of an optical scanner; the 2 contours of each patient underwent voxelization and fusion using a matrix elaborator. Outcome variables at 5 months (volumetric, surface, and linear changes) were measured in digital fused plaster casts with a dental scan software analyzing a volume of interest ranging from residual papilla to 10 mm toward the apical point. Intra‐ and inter‐group pair‐wise variables' comparisons were conducted. Level of significance was set at 0.05. Results: Twenty‐four sites were enrolled: 12 ARP and 12 naturally healed. Five‐month percentage of volume loss of the bbm ‐group (21.7% ± 7.4%) was significantly lower ( P s < .0003) than that of the naturally healing group (38.8% ± 7.9%). When tooth position was investigated, volume loss in percentage registered a significantly better ( P values ≤ .0485) behavior in molars (ΔV% = −19.1% ± 6.5% and ΔV% = −35.6% ± 7.6%, respectively, for bbm and nat ) than that in premolars (ΔV% = −26.9% ± 7.2% and ΔV% = −45.1% ± 4.2%, respectively, for bbm and nat ), in both the preserved and naturally healing groups. Conclusion: The dimensional loss in postextraction sockets grafted with anorganic bovine bone substitute and covered by a resorbable collagen barrier was lower than that of the naturally healing sites. However, ridge preservation was able to maintain almost 80% of the pristine bone.